The Process of Teaching Psychology Students to Connect with One’s Own Sensible Reality:: The Efficaciousness of Haiku Poems - Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2020)
The cognitive-behavioural model of learning is grounded on the idea that our thoughts influence our behaviours through a process of conditioning and it anticipates that whenever we can change our thoughts, our behaviours will change. This model of learning is at the foundation of the cognitive-behavioural interventions employed to treat mental health symptoms and mental health disorders. The mere abstract knowledge, separated from embodiment, about the cognitive-behavioural model of learning does not however offer to psychology students the required understanding of this conditioning process. The students need somehow to connect with one’s own sensible inner reality during the educational process. It was hypothesised that expressive arts activities, with their own alternative languages, would endow the psychology students making it easier for them to access their automatic thoughts (movements of memory). In order to test this, a procedure prompted by the SADUPA poetry technique was carried out. A qualitative analysis of the results obtained revealed changes in language associated to the Haiku expressive art activity, a growing psychological presence, awareness of one’s automatic cognitive flows, and a manifested receptivity to a more experiential based teaching.